The Effect Of Meaning In Life And Career Planning On Quarter-Life Crisis In College Students - Habibie, Alfiesyahrianta; Alvico, Rico Septian; Takdir, Annisya Muthmainnah; Alfina, Irma; Saputra, Erdin Jhaya; Ishak, Maulana (LPPM Universitas 17 Agustus 1945 Samarinda, 2025)
College students are a transition phase from late adolescence to early adulthood like physical, emotional, and social changes. For they have difficulty dealing with its will being quarter-life crisis. The meaning of life and career planning are good predictors for overcoming the difficulties experienced by college students when confront it. This study aims to empirically prove the influence of the meaning of life and career planning on the quarter-life crisis in college students. The research sample was 497 active college students in East Kalimantan aged 18-29 years. The data analysis technique used multiple linear regression with JASP application. The results of the study showed that the meaning of life and career planning had a significant effect on the quarter-life crisis with a significance level of 0.000 (p <0.05). So students need to find the meaning of life and plan their careers as early as possible in order to quickly resolve the difficulties experienced during the quarter-life crisis.Keywords:career planning, meaning life, quarter-life crisis